2004
DOI: 10.1111/j.1600-0579.2004.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of psychomotor skills of dental students at University Complutense of Madrid

Abstract: The aim of this study was to evaluate the psychomotor skills of the dental students at University Complutense of Madrid (UCM), using a battery of psychometric tests. The sample comprised 306 students of the 1st, 2nd, 3rd and 4th years of Odontology, who, during the last month of the academic term, took the test on rotation of solid shapes, the Embedded Figures test in its group form (GEFT), the O'Connor Tweezer test, the MacQuarrie test for mechanical ability and the indirect vision test. Before these tests be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…This finding complies with traditionally reported gender effects, slightly lower female scores being commonly reported Cano and Marquez, 1995;De Andres et al, 2004), due to multifaceted factors. As functional anatomy requires students to form and manipulate mental representation of a cross-section of anatomy-like structures incorporating some spatial characteristics, women were expected having greater difficulty in generating and manipulating such mental images, due to less spatial ability, as observed in numerous human cognition experiments (for review, see Jones et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This finding complies with traditionally reported gender effects, slightly lower female scores being commonly reported Cano and Marquez, 1995;De Andres et al, 2004), due to multifaceted factors. As functional anatomy requires students to form and manipulate mental representation of a cross-section of anatomy-like structures incorporating some spatial characteristics, women were expected having greater difficulty in generating and manipulating such mental images, due to less spatial ability, as observed in numerous human cognition experiments (for review, see Jones et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This fi nding is very important and in agreement with those of Gansky, 4 Luck 26 and de Andres 27 who feel that manual dexterity can be educated and improved by means of exercise and that tests to assess manual dexterity should be mainly used for identifying those subjects in need of a more careful, attentive and monitored …”
Section: Although This Study Was Not Intended To Describe a New Type supporting
confidence: 71%
“…[18][19][20][21][22][23][24][25][26][27] The formulation of exercises measur ing basic performance was inspired by a careful analysis of specifi c aspects of manual dexterity, aimed at break ing down complex behaviours into their simpler components. Therefore, exer cises investigated both specifi c abilities and the capacity to effectively combine sub-abilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study by de Andres et al. (16) showed that scores on the O’Connor tweezer dexterity test could predict poor performance of students in a preclinical dental programme. The inconsistencies in findings from these studies may be explained by the researchers choosing tests that did not sample across all abilities of skill acquisition theory (1).…”
Section: Introductionmentioning
confidence: 99%